Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Soins de longue durée en français. Rapport final - McQuaid, Steve (The Atlantic Evaluation Group Inc, 2010)

Portrait de la santé et de l’état nutritionnel des aînés francophones à domicile au Nouveau-Brunswick - Villalon, Lita (Port Acadie, 2010)
Le Nouveau-Brunswick (N.-B.) possède une des plus vieilles populations du Canada. Selon Statistique Canada (2006), 14,7 pour cent de la population du N.-B. est âgée de 65 ans ou plus. La prévention constitue la solution idéale pour assurer le vieillissement en santé. Le but de l’étude était de faire le portrait de la santé et de l’état nutritionnel des aînés à domicile au N.-B. Les objectifs spécifiques étaient de déterminer 1) le profil socio-démographique, 2) le profil de santé, 3) la situation alimentaire et 4) l’état nutritionnel. Le Mini Nutritional Assessment (MNA) et des données alimentaires ont servi à l’évaluation de l’état nutritionnel. Près de 60 pour cent des sujets ne se conforment pas à la recommandation pour les groupes lait/produits laitiers, légumes/fruits et produits céréaliers du Guide alimentaire canadien. Les apports moyens en lipides, vitamine D, folates, calcium et zinc étaient insuffisants. Plus de 50 pour cent des sujets ne couvrent pas leurs besoins en plusieurs nutriments. Selon le MNA, 15 pour cent de sujets étaient à risque nutritionnel. Cinquante-quatre pour cent des hommes et 45 pour cent des femmes ont un poids santé. Des différences ont été observées selon l’identité linguistique, soit entre francophones et anglophones, et en fonction du sexe.